presentation of research as Front Cover in the New Journal of Chemistry, Volume 46, Issue 2, Pages 470 - 479 - Drouza, Chryssoula (My University, 2026)
Honorary presentation of my work for its innovation, published under title "Four electron selective O 2 reduction by a tetranuclear vanadium(IV/V)/hydroquinonate catalyst: application in the operation of Zn–air batteries" in the New Journal of Chemistry
Keywords: Natural sciences